Patterns and Appropriateness of Antihypertensive Use in Preeclampsia: A Retrospective Study at a Jakarta Tertiary Hospital (2022-2024) - Abitmer Gultom; Hertina Silaban; Yohanes Baptistuta Paser (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Preeclampsia (PE) complicates approximately 2-8% of pregnancies worldwide and remains a leading cause of maternal and perinatal morbidity and mortality, contributing to more than 50,000 maternal deaths and nearly 500,000 neonatal deaths annually. Appropriate antihypertensive therapy is essential to prevent disease progression and adverse outcomes. This non-experimental, cross-sectional, retrospective study was conducted at the Indonesian Christian University Hospital from August to December 2024. All medical records of patients with preeclampsia during the study period were included using total sampling (N = 52). Variables included patient characteristics, type of antihypertensive therapy, and appropriateness of drug use. Appropriateness was evaluated using the 4Ts criteria (appropriate indication, appropriate drug, appropriate dose, and appropriate patient) based on the POGI 2016 guideline. Data were analyzed as proportions with 95% confidence intervals (CI), and associations between preeclampsia severity and antihypertensive patterns were explored descriptively. Most patients were aged >35 years (50%), in the third trimester of pregnancy (94.2%), and diagnosed with mild preeclampsia (80.8%). In mild preeclampsia, nifedipine monotherapy was the most frequently prescribed antihypertensive (92.9%; 95% CI: approximately 80-99%). In severe preeclampsia, nifedipine monotherapy was used in 50% of cases (95% CI: approximately 19-81%), whereas nifedipine-methyldopa combination therapy accounted for 40% (95% CI: approximately 13-74%). Evaluation of antihypertensive use showed 100% appropriateness for indication, drug selection, dose, and patient suitability, indicating entirely rational use in accordance with guidelines. Antihypertensive prescribing patterns for preeclampsia in this hospital largely adhered to clinical guidelines, with nifedipine as the mainstay therapy for both mild and severe cases. These findings support the effectiveness of guideline-based pharmacotherapy for the management of preeclampsia and highlight the need for further multicenter studies to evaluate clinical outcomes and long-term maternal-fetal safety.. Keywords: Preeclampsia, Antihypertensive Agents, Nifedipine, Drug Utilization, Pregnancy, Guideline Adherence.